THE RIVER BASIN OF IARA, CONSIDERATIONS ON THE ENERGY AND HORIZONTAL FRAGMENTATION OF THE LANDFORMS (PANGEEA, 2025)
Geographic information systems allow mapping and various and complex analyses of geographic components. The quantitative and qualitative results of depth and density analysis of fragmentation find their use in a wide range of areas, from road and rail systems building, to forest and land developments.
Keywords: Iara Basin; energy; fragmentation; density of drainage; Landform energy